(untitled) (TEST Trento Student Law Review, 2019)
In 1965, the World Bank promoted the Convention on the Settlement of Investment Disputes between States and Nationals of Other States (ICSID Convention) with the aim of filtering any political and diplomatic influence out of international investment disputes. This aim was achieved by lending several features from commercial arbitration. Today, after a successful launch phase of the Convention’s mechanism, the benefit of the current investor-state dispute settlement system is de-bated. Lack of legitimacy, interference with the states’ right to regulate in the public interest and doubts about the arbitrator’s impartiality are some examples of the most frequently voiced concerns. Several different solutions, reaching from an investment court under the CETA for the EU-Canadian disputes to a truly multilateral court available to an open number of states, have been put forward. Most of the suggested roads leading out of the ISDS crisis provide for the establishment of a standing court. Scholars primarily argue that those models bear the risk of re-politicizing the controversies. This essay assesses, based on a comparative approach, whether the concern of re-politicization is justified. For such purpose, it focuses on the areas that are particularly threatened by apossible interference of the states’ political powers: the appointment ofthe judges and their independence and impartiality requirements. The outcome of the analysis does not promise well for the future investment court. The experience of other standing courts and tribunals show that a certain degree of political influence cannot be excluded. It would rather seem that the states do not even wish to create a completely depoliticized system. In addition, as this study shows, an investment court could also widen the room for judges to introduce their political beliefs into the decision-making process.